Urban land tenure and public policy challenges: the case of access, ownership and use in Phokeng - Kadungure, Ivan (My University, 2016)
The study focuses on the lived experiences of indigenous and traditional community of Phokeng in the process of urbanising. It is a community affected by unclarified policies and documents to secure their tenure. Phokeng community in Rustenburg is approximately 200 km to the west of Johannesburg. The research revealed that the rural and marginalised of Phokeng is now becoming urbanised and that there is inadequacy of legislation or policy to guarantee security of tenure in an area a under traditional authority. The community has historically depended on oral information and storytelling. A total of thirty informants were surveyed in the community. The study elicited information on informant’s understanding of security of tenure, the role they played to secure tenure to their land. It also probed, their awareness of developmental policies affecting their activities and expectations. The study revealed that people did not have title to the land they occupied but were very content that they were safe from evictions because the traditional leader and his traditional authority provided the guarantee. There is need for further research on why people in traditional authority areas that are in the process of urbanising would be content to live on land on which they do not have registered tenure rights.
Thesis (M.M. (Public Policy))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Governance, 2016.
Keywords: Land tenure--South Africa; Land reform--South Africa--21st century